Perancangan Interior Fasilitas Edutainment Keluarga Berbasis Cerita Rakyat di Surabaya - Jessica Wirawan (Intra, 2017)
Child character education is something that can’t be developed instantly, it needs a long process and most often developed since the early stages of the children. This makes the role of parents very crucial in developing their children’s characters, but nowadays they are too busy with work to fulfill their family daily needs, therefore it affects the relationship between parents and their children becoming more distant. Therefore to strengthen the decaying relationship of parents and children, thematic edutainment facility based on folklore becomes one of the answers that provides children learning process of good characters through values that can be found in Indonesian folktales along with bonding process between parents and their children. The design method used refers to Vijay Kumar’s design thinking which was divided into 4 stages, research, analysis, synthetic, and realization.